Characteristics monitoring and analysis system development of a pem fuel cell - Pyaye, Phyo Kyaw. (2012)
The increasing integration of fuel cells with electrical and electronic systems has prompted an increase in accurate models of the polymer electrolyte membrane fuel cell (PEMFC). Advancement in technologies has allowed us the way to investigate under a wide range of possible conditions safely and economically. This project focuses on the parameters that are affecting the fuel cell performance and the experimental results on the determining the right possible capacitance value of the PEMFC using Matlab and Origin7 software.